Dieter Roth. Pages - Volpato, Elena (FLAT, 2018)
Compendium of the entire book production of Dieter Roth together with his manuscript diaries from which he drew multiple material for his works. The book carries out a careful critical analysis of a primary figure in the history of the artist's book, twenty years after his death, with the aim of restoring the importance of a work that continues to be an inexhaustible source of inspiration for the contemporary artists
Covers Dieter Roths' books, diaries, and copy books
Keywords: Roth, Dieter -- 1930-1998; Roth, Dieter / 1930-1998 / Diaries; Roth, Dieter / 1930-1998; Artists' books / 20th century / Bibliography; Pattern books / 20th century / Bibliography; Artists' books; Pattern books; 1900-1999; Bibliography; Diaries; Bildband